Neo-pentecostal mission healthcare and poverty reduction in Ghana - E. Manu (Acta Theologica, 2025)
This article explores the relationship between mission healthcare and poverty reduction, by investigating the role that Ghana’s neo-Pentecostal mission healthcare plays in the latter. Currently, in Ghana, the role of missions in health and well-being has become more diverse and impactful. Through a qualitative interpretive method, data on the role of mission healthcare in poverty reduction were gathered from leading neo-Pentecostal mission health centres in Ghana. The article reveals, among others, that neo-Pentecostal movements are into healthcare, due to the biblical basis of health which teaches them the belief that the health of others is their responsibility. The analysis reveals that the significance of the contributions of neo-Pentecostals to poverty-reducing healthcare services lies in the current concerns of not only the global agenda for sustainable development, but also the neo-Pentecostals’ sense of public responsibility towards health and well-being, which many churches identify as a fundamental prerequisite nowadays.